European cuisine and the Columbian exchange: introduction - Earle, Rebecca (Food & History, 2009)
Abstract Tomatoes, chiles, chocolate, maize and a host of other New World ingredients bear daily witness to the transformation of global eating habits that followed European colonisation of the Americas. Nonetheless, we know surprisingly little about the processes whereby these foods were naturalised into the cultural universes of their adoptive lands. This special issue of Food and History builds on the growing literature dedicated to the culinary dimensions of the Columbian exchange to offer a detailed analysis of the adoption of particular New World foodstuffs in early modern Europe. How did individual eaters respond to the new foods that curious travellers and sailors brought with them from the Indies? How does the unfamiliar become familiar? The papers that make up this dossier address these questions directly through attentive study of the incorporation of particular New World foodstuffs into the daily diets and cultural spaces of early modern Europeans. Individual articles chart the European trajectories of particular foodstuffs at the same time as they explore the methodological and theoretical frameworks within which the study of food and consumption may be situated.